2016
DOI: 10.1183/13993003.01088-2015
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy evaluation to predict oral appliance outcomes in obstructive sleep apnoea

Abstract: The objective of this study was to determine the utility of nasoendoscopy of the upper airway as a predictor of the efficacy of oral appliance treatment in obstructive sleep apnoea (OSA).A total of 61 consecutive patients with moderate-to-severe polysomnographically diagnosed OSA were recruited for this study. Using nasoendoscopy, we prospectively assessed the velopharynx and oro/hypopharynx in each patient while awake and in the supine position. We measured cross-sectional area (CSA), and anteroposterior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…13 However, a prospective study has found quantitative analysis of nasopharyngoscopic images in conjunction with baseline AHI to be predictive of OA outcome in Japanese patients with OSA. 19 In this study we wished to explore the influence of sex on OA treatment response. We targeted females in recruitment in an attempt to achieve sex balance, ending up with a 60:40 split of men and women.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, a prospective study has found quantitative analysis of nasopharyngoscopic images in conjunction with baseline AHI to be predictive of OA outcome in Japanese patients with OSA. 19 In this study we wished to explore the influence of sex on OA treatment response. We targeted females in recruitment in an attempt to achieve sex balance, ending up with a 60:40 split of men and women.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides the physiological framework for developing tools to discriminate between retropalatal and retroglossal contributions to OSA. Distinguishing between retropalatal and retroglossal airway collapse has implications for responses to therapies such as oral appliance therapy and pharyngeal surgery (11, 13).…”
Section: Discussionmentioning
confidence: 99%
“…A prediction model combining the maximum CPAP pressures and baseline AHI seemed to identify a phenotypic trait not responding to OA, predicting treatment failure with high accuracy. Other methods that examine the change of upper airways dimensions during mandibular advancement, either by sleep monitoring with the simultaneous use of a remotely controlled mandibular positioner or by endoscopic evaluation, have shown promising results [ 28 , 29 ], but are invasive and operator dependent and time and cost consuming.…”
Section: Discussionmentioning
confidence: 99%